1998
DOI: 10.1111/j.1365-2621.1998.tb15730.x
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Gelation of Brown Trout Myofibrils: Effect of Muscle Type, Heating Rate and Protein Concentration

Abstract: The thermal gelation properties of myofibril solutions (KCl 0.6M; pH 6.0) from reared brown trout white and red muscles were analyzed by thermal scanning rheometry. With a heating rate of 1°C/min, red muscle myofibrils exhibited a lower gelation capacity than white muscle myofibrils at low temperatures. No difference was observed above 60°C where solid gels were formed from the two myofibril types. Increasing protein concentration or reducing heating rate increased the values of the rheological parameters at 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 57 publications
5
18
0
Order By: Relevance
“…It has been demonstrated in previous study that as the temperature decreased, the hydrogen bonds became stronger (Foegeding, Gonzalez, Hamann, & Case, ). Increase in gel rigidity with increase in protein concentration regardless of protein type has been reported by previous studies (Lefevre, Fauconneau, Ouali, & Culioli, ; Youssef & Barbut, ). The increased exposure of hydrophobic residues at 40°C temperature provides more pitches for protein interaction, which results in formation of connected gel network (Abdollahi, Rezaei, Jafarpour, & Undeland, ; Ingadottir & Kristinsson, ; Zhao et al, ).…”
Section: Resultssupporting
confidence: 80%
“…It has been demonstrated in previous study that as the temperature decreased, the hydrogen bonds became stronger (Foegeding, Gonzalez, Hamann, & Case, ). Increase in gel rigidity with increase in protein concentration regardless of protein type has been reported by previous studies (Lefevre, Fauconneau, Ouali, & Culioli, ; Youssef & Barbut, ). The increased exposure of hydrophobic residues at 40°C temperature provides more pitches for protein interaction, which results in formation of connected gel network (Abdollahi, Rezaei, Jafarpour, & Undeland, ; Ingadottir & Kristinsson, ; Zhao et al, ).…”
Section: Resultssupporting
confidence: 80%
“…During study of the gelation properties of chicken and turkey white and red muscle myofibrils, Lesiów and Xiong (2001a) concluded that red muscle formed weaker gel than white one. Similar differences were seen in the study of Lefévre and others (1998) on reared brown trout, where, at a heating rate of 1 °C/min, the thermal gelation properties of red muscle myofibrils exhibited a lower gelation capacity than white muscle myofibrils. No differences were observed above 60 °C where solid gels were formed from both myofibril types.…”
Section: Type and Source Of Musclesupporting
confidence: 83%
“…In the case of fish paste, G ′ started to increase from 5 °C, reaching the 1st peak at 35 °C, indicating the transformation from a viscous sol to an elastic network (Egelandsdal and others 1986). The initial increase of G ′ to 35 °C could be related to interactions that occur at low temperatures between protein molecules (Lefèvre and others 1998; Lanier and others 2004). Subsequently, G ′ dropped abruptly, reaching a minimum at 51 °C.…”
Section: Resultsmentioning
confidence: 99%